Solid solution hardening effects on structure evolution and mechanical properties of nanostructured binary and high entropy alloys after high pressure torsion. Issue 1 (1st July 2022) - Keil, T; Minnert, C; Bruder, E; Durst, K
Abstract: Two different alloy series (Cu-X, Ni-X) have been selected to investigate the effects of solutes on the saturation grain size, the thermal stability and mechanical properties after high pressure torsion. The results of the Cu-X series indicate that the saturation grain size does not correlate with the stacking fault energy but shows good agreement with solid solution hardening according to the Labusch model. This correlation does not only hold for binaries, but also for chemically complex high entropy alloys (Ni-X) in the form of (CrMnFeCo)x Ni1-x, where the Varvenne model is used to describe solid solution hardening. The alloy series exhibit a grain size in the range of 50 – 425 nm after high pressure torsion and the solutes increase the strength as well as the thermal stability of the alloys after annealing. The nanostructured alloys exhibit an enhanced strain rate sensitivity exponent, as determined from nanoindentation strain rate jump and constant contact pressure creep testing, whereas an enhanced rate sensitivity is found at low strain rates. The relatively lower rate sensitivity of the alloys as well as their higher thermal stability indicate, that defect storage and annihilation is strongly influenced by a complex interaction of solutes, dislocations and grain boundaries.